The role of systemic hypermobility and condylar hypermobility in temporomandibular joint dysfunction syndrome - Kavuncu, V; Sahin, S; Kamanli, A; Karan, A; Aksoy, C (Springer, 2006)
Objective: To evaluate the risk of temporomandibular joint dysfunction (TMD), when both systemic joint hypermobility (SJH) and localized condylar hypermobility (LCH) exist. Materials and methods: Sixty-four consecutive outpatients with temporomandibular joint clicking or pain, and 77 sex- and age-matched control subjects, were recruited in the study. LCH was diagnosed when condylar subluxation was present, and SJL was diagnosed by using Beighton's method. The frequency of symptoms, mean mouth opening, and the frequency of subjects with SJL and LCH were the main outcome measures. Results: Out of the 64 patients, 16 patients were suffering from pain, 20 patients from joint-clicking and 28 patients from both. Both SJH and LCH were more frequently observed in those patients with TMD than in control subjects. The risk of TMD was higher if LCH and SJH existed jointly. Conclusion: Both systemic and localized hypermobility may have a role in the etiology of TMD.
Keywords: temporomandibular joint dysfunction; hypermobility